Pendidikan Pondok Pesantren: Institusionalisasi Kelembagaan Pendidikan Pesantren - Rusydi Sulaiman (Institut Ilmu Keislaman Annuqayah, 2016)
Pondok Pesantren has a spesific tradition that is far different with other institutions. It has sub-culture relating with way of life, system of values, system of power and authority in its administration. As the oldest education in Indonesia, it has at least five pillars, namely kiyai, santri, mosque, boarding house and kitab kuning. The modernization has changed the sub-culture and pillars. The models of modern education changed the sub-culture. This article describes that Pondok Pesantren as educational institution has basic aspects called “Falsafah and Idealisme”, consist of basic values, pesantren’s tradition and its spirit (ruh al-Ma‘had). Pesantren then comes forward to strenghen its institution—promoting Ma’had ‘Aly and university concept. Biside conserving its traditional values, pondok pesantren should be accomodative toward next valuable thing (al-Muha>fazah ‘ala al-Qadi>m al-Sa>lih wa al-Akhzb̆i al-Jadi>di al-Aslah). There are some aspects should be strenghened in pesantren: academic, administrative, net-working and so on. It is regarding that pesantren as fortresses for the defence of Islamic community and centres for dissemination of Islam.